DFT based study on structural stability and transport properties of Sr3AsN: A potential thermoelectric material. Issue 15 (14th August 2019) - Haque, Enamul; Hossain, M. Anwar
Abstract: Abstract : Antiperovskite materials are of high research interest because of their unusual physical properties and technological applications. Here, we report the structural stability and transport properties of Sr3 AsN from first-principles study. The calculated equilibrium lattice parameters are in good agreement with the available data. We find that Sr3 AsN is mechanically, energetically and dynamically stable at ambient conditions. Our calculated electronic structure indicates that it is a direct band gap semiconductor, with a band gap value ∼1.2 eV. Sr-4 d and N-2 p orbitals predominantly contribute to the formation of the direct band gap. The calculated Seebeck coefficient of Sr3 AsN is high (298 μV/K at 300 K), while the lattice thermal conductivity is comparatively low (1.73 W/m K). The considerable mass difference between Sr, As, and N gives rise to an intense phonon scattering that results in such low lattice thermal conductivity. Our calculated maximum thermoelectric figure of merit ( ZT ) is 0.75 at 700 K, indicating that it is a potential material for thermoelectric device applications.